Production of Prodigiosin Using Tannery Fleshing and Evaluating Its Pharmacological Effects. (23rd January 2014) - Sumathi, C.; MohanaPriya, D.; Swarnalatha, S.; Dinesh, M. G.; Sekaran, G.
Abstract : Aim . The focal theme of present investigation includes isolation of prodigiosin producing fish gut bacteria, enhancing its production using tannery solid waste fleshing, and evaluation of its pharmacological effect. Methods . Optimization of fermentation conditions to yield maximum prodigiosin, and instrumental analysis using FTIR, NMR, ESI-MS, TGA, and DSC. Results . The optimum conditions required for the maximum prodigiosin concentration were achieved at time 30 h, temperature 30°C, pH 8, and 3% substrate concentration. The secondary metabolite was analyzed using ESI-MS, FTIR, and NMR. Therapeutic efficacy was assessed by in vitro anticancer studies. Among the pathogenic bacteria Pseudomonas aeruginosa was most susceptible at the lowest concentration followed by Salmonella typhi. IC50 concentration was cell line specific (HeLa cells: 4.3 µ M, HEp2: 5.2 µ M, and KB cells: 4.8 µ M) and remains nontoxic up to the concentration of 25 µ M on normal Vero cells suggesting that cancerous cells are more susceptible to the prodigiosin at lower concentration. Conclusion . Maximum prodigiosin production was obtained with tannery fleshing. The potency of the fish gut bacterial secondary metabolite prodigiosin as a therapeutic agent was confirmed through in vitro antimicrobial and anticancer studies.